Economic Weights in Rabbit Meat Production - Cartuche, L.; Pascual, Mariam; Gómez, Ernesto A.; Blasco, A. (2017)
A profit function was designed for an industrial commercial rabbitry with the most common management in industrial rabbit production. The incomes, costs, and profit function were calculated and economic weights of the traits were estimated. The variable costs (feeding, artificial insemination, health and replacement) represented 62% of the total costs, and the fixed costs (labour, utilities, amortisation and administration) represented 38% of the total costs. Major costs were feeding of fattening kits and labour cost, at 26% and 18% of the total cost, respectively. The economic weights were feed conversion rate during fattening (-20.2 (sic)/[g feed/g liveweight]), number of kits born alive (15.7 (sic)/kit), pregnancy rate (1.7 (sic)/percentage unit), weaning survival (1.7 (sic)/percentage unit), fattening survival (2.0 (sic)/percentage unit), daily feed intake (-0.50 (sic)/(g feed/d)), daily gain during fattening (1.33 (sic)/(g weight/d)), and replacement rate (-0.29 (sic)/percentage unit). When varying the prices of kg of fattening feed and kg of liveweight, only the economic weights of feed conversion rate during fattening in the first case and the number of kits born alive in the second case changed considerably. Changes in labour cost produced appreciable changes in the whole production cost. Although economic weights are robust to changes in prices, these weights should be recalculated after some generations of selection, because changes in the mean of the traits due to selection can also change economic weights.